THE INFLUENCE OF PROBLEM-BASED LEARNING METHOD ON THE LEOPOLD MANEUVER CLINICAL SKILL IN DIPLOMA MIDWIFERY STUDENTS - Ani T Prianti; Nurhaedar Jafar; Mardiana Ahmad (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: In dealing with the current condition of the Covid-19 pandemic, the education system finds the alternative and changes the regular learning to an online system. This online system depends on vital aspects such as well-structured, interactive, and substantive programs. Consequently, educators are challenged to be more frequently innovative and active in assessing and evaluating learning needs. Implementing a proper learning method helps to encourage students' willingness to learn since they are the core of the learning process. Therefore, this research considered Problem-based Learning as a suitable learning method to implement and improve clinical skills. By learning from a problem, students are indirectly instructed to learn how to collect and integrate new knowledge. Objectives: This study focuses on determining the implementation of Problem-Based Learning methods on the Leopold maneuver antenatal midwifery care subject in the diploma midwifery students. Methods: This study uses a quasi-experimental design with a one group pretest-posttest design. The samples in this study are 30 students from Megarezky University. Data are analyzed by univariate and bivariate with chi-square test. This study uses a questionnaire to measure students' interest and motivation in participating in learning in antenatal care courses, and to measure skills in performing the Leopold maneuver using a standardized checklist from the Antenatal Care Module of the Ministry of Health. This research is conducted within two months (December to January 2022). Results: The result reveals that the Problem-Based Learning Method (PBL) effectively increases the score of students' clinical skills with a p-value: 0.000 < 0.05. Conclusion: Problem-Based Learning Method (PBL) effectively improves the clinical skills of Leopold maneuver Antenatal care.